Analisis Ketersediaan Fasilitas Kerja di Perpustakaan Daerah Kabupaten Aceh Tengah dengan Menggunakan Pendekatan Studi Ergonomi - Nuri Ifka Bengi; Cut Putroe Yuliana (Jurnal Adabiya, 2020)
This study is entitled "Analysis of the Availability of Work Facilities in the Central Aceh District Library Using the Ergonomic Study Approach". The formulation of the problem in this research is how the availability of work facilities in the Central Aceh District Library using an ergonomic study approach. The purpose of this study is to determine the ergonomics standards in work facilities available in Central Aceh District Library. This study used qualitative research methods. Data collection through observation and interviews. The subjects in this study were librarians who worked in the library as many as 14 people. While the objects in this study are work facilities that include work chairs, work desks, collection racks and cabinets. The results showed that work facilities that had met ergonomic standards were tables and chairs. Meanwhile, collection racks, work cabinets and reference cabinets are not included in the ergonomics category and there are complaints of fatigue on the shoulders, waist and neck.